Temporary Contractors & Full-Time Employees: : Contextually Driven Decision-Making and the Customer Experience in Higher Education Information Technology - Hooke M.S.L.A., C.T.S. University of Maine, Drew Thompson (Journal of Marketing Communications for Higher Education, 2021)
Colleges and universities face an increased number of technology-reliant events and activities yet often do not have the in-house event services staff to meet the demand for technology support. Many institutions hire contractors temporarily to fill this gap, as opposed to hiring additional permanent staff. The issue with contracted labor is that such personnel are temporary, implying a perpetual state of newness. Contractors will not have the institutional knowledge of their permanent staff counterparts and will not be empowered to make the same decisions. Additionally, contractors will not have the same keys, access, or geographical knowledge of the campus. They will likely not be invested in the college community to the same degree as their permanently employed colleagues. Furthermore, institutions often cannot invest in temporary contractors in the ways they can with permanent full-time employees. Customer service, engagement, relationship building, and overall quality of service often suffer as a result. Customer engagement is an integral part of any higher education institution. The interface between staff and clientele within information technology services and event support is crucial to a college campus's successful operation and is cited in academic sources as among the most critical drivers of clientele satisfaction and student/customer retention. This research project aims to explore a primary factor impacting customer service within higher education information technology as well as the positive and negative effects that full-time employees and temporary contractors can have on the higher education customer experience.